Telling Stories Differently: Engaging 21st Century Students Through Digital Storytelling - Janet Condy (African Sun Media, 2015)
The aim of this book is to share a relatively loose collection of studies using digital storytelling as a pedagogical tool in Cape Peninsula University of Technology (CPUT). The book takes an informed social justice approach to teaching and learning, at the heart of which is the exploration of DST as a practice of voice and agency. Voice and agency are important in excavating and recovering subjugated identities, and moving the concerns of those occupying subaltern spaces to the mainstream of teaching and learning. Yet this discursive shift is not without inherent challenges. Multi-modal technologies are reflective of wider inequities in the so-called technological divide. Whilst this is a book about higher education, there are important lessons for schooling. On the one hand, the book is a powerful demonstration of the potential of DST for enhancing learning in schools, particularly in schools serving the poor and marginalised. On the other hand, improving teaching and learning in higher education, through the creative use of technology, is essential to overcome the learning challenges of those entering tertiary level institutions.